2022
DOI: 10.3389/fpsyg.2022.921161
|View full text |Cite
|
Sign up to set email alerts
|

How workplace incivility leads to work alienation: A moderated mediation model

Abstract: Workplace incivility remains a prevailing issue and has significant potential for harmful consequences. This study aims to investigate the influencing mechanism of workplace incivility on work alienation from the perspective of targets. Based on the social exchange theory, our research examines the role of interpersonal trust as a mediator along with the moderator of career resilience in the said association. Through a two-wave-time-lagged quantitative research design, a sample of 315 nurses from China was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 112 publications
1
3
0
Order By: Relevance
“…Our research results demonstrate that Chinese clinical nurses had a moderate level of work alienation, with an overall score of 34.64 ± 10.09, similar to Xia’s findings [ 17 ], But higher than Cui’s study of nurses in northwest China [ 42 ]. We believe that a number of reasons account for this: (1) Although all were in the context of a pandemic, differences in the timing of the survey, the region studied, the intensity of the epidemic, the strains of infection, and the preventive and control measures taken may have led to differences in the number of infections, psychological stress and nurses’ workload, resulting in heterogeneity in the nurses’ sense of alienation from their work.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our research results demonstrate that Chinese clinical nurses had a moderate level of work alienation, with an overall score of 34.64 ± 10.09, similar to Xia’s findings [ 17 ], But higher than Cui’s study of nurses in northwest China [ 42 ]. We believe that a number of reasons account for this: (1) Although all were in the context of a pandemic, differences in the timing of the survey, the region studied, the intensity of the epidemic, the strains of infection, and the preventive and control measures taken may have led to differences in the number of infections, psychological stress and nurses’ workload, resulting in heterogeneity in the nurses’ sense of alienation from their work.…”
Section: Discussionsupporting
confidence: 85%
“…Studies in Spain, Italy and Pakistan showed high rates of work alienation [ 14 – 16 ]. Research also noted that nurses are prone to experience work alienation because of work overload and occupational risks [ 17 ]. More importantly, the study pointed out that employees performed poorly at work or even showed anti-productive behaviour when they had stronger feelings of alienation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, budgetary restrictions, understaffing, and bureaucratic inefficiencies in public organizations can all lead to higher levels of stress and employee alienation from their workloads (ÜMİT & Aysel, 2022). Fourth, pressures to fulfill profit targets, stay competitive, and satisfy productivity standards can also result in higher workloads and job stress in private organizations (Xia, Wang, Li, He, & Wang, 2022).…”
Section: Workloadmentioning
confidence: 99%
“…Workplace incivility affects employees' sales performance (Sliter et al, 2012), job satisfaction and turnover intention (Chen & Wang, 2019;Han et al, 2016;Parray et al, 2023), absenteeism (Sliter & Boyd, 2015), counterproductive work behavior (Sakurai & Jex, 2012;Zahoor et al, 2019), job performance (Rhee et al, 2017), physical health (Cortina et al, 2022;Jorgensen et al, 2023), sleep quality (Demsky et al, 2019), unhealthy eating behavior (Liu et al, 2017) and maladaptive shopping behavior (Song et al, 2018). Workplace incivility also leads to work alienation (Xia et al, 2022), workplace loneliness (Kuriakose et al, 2023), emotional exhaustion (Sliter et al, 2010), psychological distress (Adams & Webster, 2013), marital dissatisfaction (Ferguson, 2012) and work-family conflict (WFC) (Lim & Lee, 2011;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%